THERAPEUTIC COMMUNICATION AND PATIENT SATISFACTION LEVEL IN CHRONIC KIDNEY FAILURE IN THE HEMODIALYSIS ROOM - larira, dina mariana; Nurmansyah, Muhamad; Pondaag, Ferlan A. (E-Jurnal Medika Udayana; Vol 13 No 9 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i09.P11, 2024)
Therapeutic communication is an interaction conducted by nurses with patients based on mutual trust which aimed to improving the emotional and physical problems of the patient. The complexity of problems experienced by chronic kidney failure patients due to hemodialysis therapy certainly requires support from nurses to assist patients in coping with it, thus requiring solutions to address these problems by providing support both emotionally and spiritually to patients through communication and building a therapeutic relationship with patients. This study aims to determine the relationship between therapeutic communication and the level of satisfaction of chronic kidney failure patients in the hemodialysis room of RSUP Prof. Dr. R. D. Kandou Manado. The study used descriptive analytical methods with a cross-sectional design. The sample used consisted of 145 respondents using accidental sampling. From the chi-square test analysis, a p-value of < 0.001 was obtained, meaning that there is a relationship between nurse's therapeutic communication and the level of satisfaction of chronic kidney failure patients at RSUP Prof. Dr. R.D. Kandou Manado.